Facility management at drug rehabilitation centre in Selangor / Nurul Hafizah Mohd Ramli - Mohd Ramli, Nurul Hafizah (Faculty of Architecture, Planning and Surveying, 2009)
Facility Management (FM) is a process to achieve the objective and aim of an organisation with fulfill the customer needs, attempt to improve the quality, reduce risk which is mainly strategy to achieve their organisation aim. Rehabilitation centre is an organization providing the facility to their occupant. Rehabilitation centre or PUSPEN (Pusat Pemulihan Penagihan Nakotik) is one of government institution existed to help those drug addict. It is one of government exertion to overcome drug problems in Malaysia. A lot of treatment and facilities provided by the rehabilitation centre, but there are still having an argument how impressive the centre in order to rehabilitate them. The latest statistic shown, numbers of continuous drug addict is higher than new cases, sources from AADK (National Anti Drug Agency). According to chief director of AADK Datuk Hamzah Abdullah (Bernama 2004), lack of training staff and increasing number of the victims will affect the using of the facilities and the current management staff. This purpose of this research was to identify the facilities provided in rehabilitation centre and to investigate their maintenance management applied. The research find that about 65% of respondents agreed the facilities provided insufficient and 95% of them said there are no proper maintenance management in the centre. Others are to suggest and comment some possible changes which could benefit in the future.